2021
DOI: 10.1016/j.str.2020.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A conformational change in the N terminus of SLC38A9 signals mTORC1 activation

Abstract: mTORC1 is a central hub that integrates environmental cues, such as cellular stresses and nutrient availability to modulate metabolism and cellular responses. Recently, SLC38A9, a lysosomal amino acid transporter, emerged as a sensor for luminal arginine and as an activator of mTORC1. The amino acid-mediated activation of mTORC1 is regulated by the N-terminal domain of SLC38A9. Here, we determined the crystal structure of zebrafish SLC38A9 (drSLC38A9) and found the N-terminal fragment inserted deep within the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Using groups of amino acids to activate mTORC1 in un-injected oocytes, we found an intriguing coincidence between the substrates of SNAT2 and their ability to activate mTORC1. The extended N-terminus of slc38 member SNAT9 has recently been shown to bind to the RagA/C heterodimer (Rebsamen et al, 2015;Wang et al, 2015;Fromm et al, 2020) and occupy the arginine binding site during mTORC1 inactivation (Lei et al, 2018;Lei et al, 2020). A similar mechanism could be envisioned for the N-terminus of SNAT2 (Gaccioli et al, 2006;Hundal and Taylor, 2009;Poncet and Taylor, 2013), although the N-terminal is predicted to be 50 residues shorter than that of SNAT9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using groups of amino acids to activate mTORC1 in un-injected oocytes, we found an intriguing coincidence between the substrates of SNAT2 and their ability to activate mTORC1. The extended N-terminus of slc38 member SNAT9 has recently been shown to bind to the RagA/C heterodimer (Rebsamen et al, 2015;Wang et al, 2015;Fromm et al, 2020) and occupy the arginine binding site during mTORC1 inactivation (Lei et al, 2018;Lei et al, 2020). A similar mechanism could be envisioned for the N-terminus of SNAT2 (Gaccioli et al, 2006;Hundal and Taylor, 2009;Poncet and Taylor, 2013), although the N-terminal is predicted to be 50 residues shorter than that of SNAT9.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple transporters have been advanced as direct or indirect activators of the mTORC1 pathway including SNAT2 (slc38a2) (Evans et al, 2007;Hyde et al, 2007;Evans et al, 2008), SNAT9 (slc38a9) (Rebsamen et al, 2015;Wang et al, 2015), LAT1-4F2hc (slc7a5-slc3a2) (Fuchs et al, 2007;Nicklin et al, 2009), ASCT2 (slc1a5) (Fuchs et al, 2007;Nicklin et al, 2009), PAT1 (slc36a1) (Heublein et al, 2010;Zoncu et al, 2011;Wu et al, 2016;Zhao et al, 2019) and PAT4 (slc36a4) (Heublein et al, 2010;Fan et al, 2016;Zheng et al, 2016). A number of studies have now firmly established that SNAT9 is a lysosomal arginine sensor for mTORC1 (Jung et al, 2015;Rebsamen et al, 2015;Wang et al, 2015;Rebsamen and Superti-Furga, 2016;Wyant et al, 2017) by direct interaction of the transport N-terminal with the Rag GTPase-Ragulator-FLCN:FNIP2 complex upon arginine sensing (Fromm et al, 2020;Lei et al, 2020). Another widely proposed mechanism is glutamine accumulation by ASCT2, followed by its exchange for leucine import via LAT1-4F2hc (Fuchs et al, 2007;Nicklin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Their study unveils a plug-and-socket mechanism where a flexible protruding loop of the complex plugs into the central cavity of the transporter, suggesting a mechanism for the interplay between amino acid transport and amino acid signaling. Interestingly, this mechanism bears some resemblance with the interaction between another lysosomal amino acid transporter and a signaling complex intervening in the mechanistic target of rapamycin complex 1 (mTORC1) pathway elucidated in very recent studies (6,7).…”
mentioning
confidence: 83%
“…The large, cytosolic N-terminal tail of SNAT9 had been implicated in the interaction with the Ragulator-Rag complex (12,13); however, the arginine-sensing mechanism remained unclear. In a recent study (7), part of the N terminus was shown to form a β hairpin, which plugs into the central cavity of SNAT9 in cytosol-open conformation and interacts with the arginine-binding pocket at the bottom of the cavity. Arginine competes with the β hairpin, thus releasing it from the central cavity with two outcomes: The amino acid transport activity of SNAT9 is up-regulated because alternating-access movements are not hindered anymore, and the N-terminal tail of SNAT9 can engage in other interactions (Fig.…”
Section: Nutrient Sensing By Mtorc1 At the Lysosomal Surfacementioning
confidence: 99%
“…GTPases involved in downstream signaling [78,92]. In a potential case of convergent evolution, the C-terminal domain of the pH-dependent Glu/GABA exchanger GadC arrests transport by binding to the intracellular cavity at neutral pH in a nearly identical conformation [48].…”
Section: Structural Diversity Outside the Ten-helix Corementioning
confidence: 99%